Risk Factors, Prevalence and Epidemiology of Prostate Cancer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents information from foreign sources about the factors and epidemiology of prostate cancer. Information on the importance and influence of risk factors for prostate cancer, including genetic factors, poor-quality diet, chemical drug exposure, infections, sexual activity, and ethnicity, was obtained from the National Cancer Institute (NCI) database.